From doctor to facilitator: reflecting on the metaphors of early career EFL teachers. Issue 1 (2nd January 2023) - Farrell, Thomas S. C.
ABSTRACT: When language teachers enter a classroom to teach in their early career years, they hold many different beliefs and feelings about how to conduct their classes that for the main part remain at the tacit level of understanding. However, it is important for early career language teachers to become aware of these beliefs and feelings so that they can critically reflect on their significance during this challenging period. Metaphors can offer early career teachers a rich means of identifying their experiences and beliefs that underpin their understanding of teaching and learning a second or foreign language. This qualitative study sought to contribute to the discussion of the experiences of four early career English as a foreign language (EFL) teachers through their use of metaphors to describe their personal understanding of their beliefs and feeling. Specifically, the case study examined the metaphors used by one teacher in her 2nd year, another in his 3rd year an additional teacher in his 4th year, and one in his 5th year of teaching. Results indicate that teachers in their 2nd and 3rd years chose personal metaphors that 'diagnose' deficits and thus must be in control, while in their 4th and 5th years the teachers wanted to motivate and facilitate the learning process rather than control it.